2013
DOI: 10.1039/c3dt00115f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced WO3/g-C3N4 composites with enhanced photocatalytic activity

Abstract: Novel WO3/g-C3N4 composite photocatalysts were prepared by a calcination process with different mass contents of WO3. The photocatalysts were characterized by thermogravimetric analysis (TG), powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (EDS), high-resolution transmission electron microscopy (HRTEM), UV-vis diffuse reflection spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), photoluminescence (PL) and electrochemical impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
248
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(263 citation statements)
references
References 60 publications
12
248
1
2
Order By: Relevance
“…Herein, the PL spectra of pure g-C 3 N 4 and Ta 3 N 5 /g-C 3 N 4 composites were excited by irradiation of wavelength 350 nm. It can be seen that the main PL emission peak of pure g-C 3 N 4 is at about 460 nm, because the energy of emission light resembles to the E g of g-C 3 N 4 [51], which is in agreement with the result of the UV-vis analysis. When Ta 3 N 5 was combined with g-C 3 N 4 , the emission intensity of Ta 3 N 5 /g-C 3 N 4 composites observed is smaller than that of pure g-C 3 N 4 with the emission peak at nearly the same position, and 2-Ta 3 N 5 /g-C 3 N 4 sample has the weakest intensity.…”
Section: Charge Transfer and Separation Propertiessupporting
confidence: 79%
“…Herein, the PL spectra of pure g-C 3 N 4 and Ta 3 N 5 /g-C 3 N 4 composites were excited by irradiation of wavelength 350 nm. It can be seen that the main PL emission peak of pure g-C 3 N 4 is at about 460 nm, because the energy of emission light resembles to the E g of g-C 3 N 4 [51], which is in agreement with the result of the UV-vis analysis. When Ta 3 N 5 was combined with g-C 3 N 4 , the emission intensity of Ta 3 N 5 /g-C 3 N 4 composites observed is smaller than that of pure g-C 3 N 4 with the emission peak at nearly the same position, and 2-Ta 3 N 5 /g-C 3 N 4 sample has the weakest intensity.…”
Section: Charge Transfer and Separation Propertiessupporting
confidence: 79%
“…It indicated that In 2 O 3 /C 3 N 4 (17.3%) composite had lower resistance than that of C 3 N 4 . This result confirmed that the introduction In 2 O 3 into C 3 N 4 can enhance the separation and transfer efficiency of photogenerated electron-hole pairs [44], which was benefit to the enhancement of photocatalytic activity.…”
Section: Photocurrent and Eis Analysissupporting
confidence: 74%
“…The calculated top VB and bottom CB of In 2 O 3 were 2.12 eV and −0.56 eV, respectively. For C 3 N 4 , the top VB and the bottom CB were 1.57 eV and −1.13 eV, respectively [44]. Upon irradiated by visible light (>400 nm), both In 2 O 3 and C 3 N 4 can be activated in the composites.…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, in the synergism of WO 3 -g-C 3 N 4 , the former component helps to reduce the recombination rate of electron-hole pairs while the latter one enhances the active sites of the catalyst surface. 43,44 Herein, we have presented for the first time a morphology-based novel WO 3 -g-C 3 N 4 (1D/2D) synergetic hybrid system fabricated by a simple hydrothermal and annealing method which exhibited superior photocatalytic activity and stability for the degradation of RhB under visible light irradiation. It can be found that after mixing g-C 3 N 4 with WO 3 , the catalytic efficiency and photo stability of the WO 3 microrods were substantially improved.…”
Section: Introductionmentioning
confidence: 99%